PENINGKATAN PEMAHAMAN MASYARAKAT DALAM PENYAMBUTAN BULAN SUCI RAMADHAN PADA DESA TAMBISKI NAULI KABUPATEN MANDAILING NATAL - Azhar Nasution; Edriagus Saputra; Naimah Hasanah; Husni Ismail; Anni Marhamah; Aisyah Aisyah; Syafri Martabe Rizka Nasution (Institut Agama Islam Sumatera Barat, 2026)
This community service activity aimed to enhance religious understanding, spiritual preparedness, and social solidarity among community members in welcoming the holy month of Ramadan. The program was conducted on Saturday evening, February 14, 2026, after the Isha prayer at Masjid Al-Hilal, targeting the residents of Tambiski Village. The main speaker was Azhar Nasution, M.Ag., accompanied by a team of lecturers from Sekolah Tinggi Agama Islam Negeri Mandailing Natal. The activity employed lecture-based, participatory, educational, and religio-cultural approaches, positioning the community as both the subject and the object of the program. The results indicated an increase in public understanding of the importance of physical and spiritual preparation before entering Ramadan. This was reflected in the participants’ enthusiasm throughout the activity, especially during the discussion and question-and-answer session, which focused on recommended sunnah practices, fasting etiquette, spiritual preparation, and ways to cultivate a worshipful atmosphere within the family. The attendance of participants from various social groups demonstrated strong community engagement and support for religious activities in the village. The program also generated positive social impacts, including greater motivation among younger generations to participate in religious activities, strengthened social relationships among residents, and the growth of a spirit of mutual cooperation. Overall, this community service activity successfully served as a medium of religious education, spiritual motivation, and reinforcement of socio-religious values in welcoming Ramadan